ベイコク フランス ドイツ オヨビ ニホン ノ ナイリク トラバース ノ ゲンジョウ - 石沢, 賢二; イシザワ, ケンジ; Ishizawa, Kenji (2008)
P(論文) 南極大陸で日本南極地域観測隊が実施してきた内陸トラバース輸送と,米国,フランス,ドイツが行っている最近の輸送形態をレビューした.雪上車や牽引トラクターについては,重量,牽引力,速度,燃料消費率などの性能を比較した.橇については,スキーの形状,接地圧,牽引方法,軟雪地帯での走行方法などについても調査した.さらに,キャンプでの生活方法などにも言及した.最後に,各国の現状を参考にして今後日本隊が研究・開発しなければならない新しい輸送方法について考察を行い基本的な態勢を提案した. Inland traverses conducted by the Japanese Antarctic Research Expedition (JARE) and the other countries (USA, France and Germany) are reviewed. The performances such as weight, traction force, speed and fuel consumption of the tractors and snow vehicles are compared. The usage of various types of sledges is examined and driving operation on soft snow surface is also described. Furthermore the method of camping is explained. Finally, a new traverse system that JARE has to study and develop is discussed. The author proposes a basic transportation system for the future, incorporating the technology used by other countries. departmental bulletin paper